Keterlaksanaan Pembelajaran Model Constructivist Teaching Sequence (CTS) Berbantuan Augmented Reality (AR) Pada Materi Konsep Sel - Malanua, Halima Y.; Latjompoh, Masra; Usman, Nurul Fajryani; Husain, Ilyas H.; Akbar, Muh. Nur (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2025)
This study aims to describe the implementation of the Constructivist Teaching Sequence (CTS) learning model supported by Augmented Reality (AR) media on cell concept material. The main focus is to evaluate the extent to which each stage in the syntax of the CTS model can be implemented properly during the learning process. This study used a quantitative descriptive approach with a learning implementation observation instrument. The research subjects were 25 students of class XI SMA Negeri 1 Gorontalo. The results showed that the exploration, restructuring, and evaluation stages were optimally implemented with percentages reaching 100%, 97%, and 100%, respectively. The introduction stage is at 80%, while the application of new concepts still needs to be improved with 70% implementation. The overall average of learning implementation reached 89%, which is included in the excellent category. This finding indicates that the AR-assisted CTS model is very feasible to be applied to support students' active involvement and concept understanding.